2017
DOI: 10.1002/ajim.22708
|View full text |Cite
|
Sign up to set email alerts
|

Work‐related musculoskeletal disorder surveillance using the Washington state workers’ compensation system: Recent declines and patterns by industry, 1999‐2013

Abstract: As documented in other North American contexts, this study describes an important decline in the incidence of WMSDs. The Washington State workers' compensation system provides a rich data source for the surveillance of WMSDs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(25 citation statements)
references
References 24 publications
2
20
0
Order By: Relevance
“…These findings are consistent with those previously reported using data from the 2010 National Health Interview Survey, which estimated that the prevalence of CTS was higher among women, and that the highest ratios of CTS cases to percentage of workforce were among production, office and administrative support, and personal care and service occupations (2.5%, 1.66%, and 1.53%, respectively) ( 4 ). A study using Washington State workers’ compensation claims reported an annual decrease of 6.2% CTS incidence during 2002–2013, similar to the decrease in this analysis ( 5 ). A pooled analysis of six prospective cohorts documented CTS incidence among 50 workgroups of 2.3 cases per 100 person-years, which is higher than the incidence estimates in this analysis ( 6 ).…”
Section: Discussionsupporting
confidence: 80%
“…These findings are consistent with those previously reported using data from the 2010 National Health Interview Survey, which estimated that the prevalence of CTS was higher among women, and that the highest ratios of CTS cases to percentage of workforce were among production, office and administrative support, and personal care and service occupations (2.5%, 1.66%, and 1.53%, respectively) ( 4 ). A study using Washington State workers’ compensation claims reported an annual decrease of 6.2% CTS incidence during 2002–2013, similar to the decrease in this analysis ( 5 ). A pooled analysis of six prospective cohorts documented CTS incidence among 50 workgroups of 2.3 cases per 100 person-years, which is higher than the incidence estimates in this analysis ( 6 ).…”
Section: Discussionsupporting
confidence: 80%
“…Second, most medical care workers in China are very busy - some doctors can see up to 100 patients a day - and sonographers in China have been reported to scan more patients than do sonographers in the other countries because of the workforce shortage 11) . Third, WRMSDs are compensable injuries in most developed countries, while WRMSDs are not compensable injuries in China 12 , 13) . Hence, little attention is paid to the prevention of WRMSDs among sonographers in China, and the self-protection awareness of sonographers is low.…”
Section: Introductionmentioning
confidence: 98%
“…Work-related musculoskeletal disorders are seldom life threatening but do cause loss of labor time, lower the quality of life, increase financial burden, and are a major public health problem. For example, in the state of Washington from 1999 to 2013, WRMDs accounted for more than 40% of all workers' compensation claims (Marcum & Adams, 2017). In Great Britain in 2016-2017, ~8.9 million working days were lost due to WRMDs.…”
Section: Introductionmentioning
confidence: 99%